A capoeira no período da ditadura militar (1964-1985) no contexto de Belo Horizonte - MG: diálogos acerca dos processos de resistência e enquadramento na prática da capoeiragem - Leonardo Fernando de Jesus (2015)
The Capoeira is a mixed fight, dance and play, that articulates different aspects of cultural practice in the subjectivy process constituent subject in moment expression. This work aims to research and discuss, throug historical, documentary studies, Masters of reports that Afro-Brazilian cultural practice, among other methodological strategies, as capoeiristas did their struggle a leisure option through a mix of strength and framework towards na authoritarian regime. During the period of Military Dictatorship, some Capoeiras wheel taking place on the streets or in the squares of Belo Horizonte, were guarded by police sometimes undecover, when the Police suspected that Wheel submit a subversive character, the weel was reprimanded and bound up some capoeiras. In the early 70s, Capoeira was already taking over the country and consequently happened, what I will call capoeiras export, because this time, many capoeiristas of São Paulo and Rio middle class, were giving Capoeira classes abroas, initially US and soon Europe, already in the 80s, capoeiristas miners began to venture in foreing lands. It is felt that the period of the Military Regime hás brought several changes in Capoeira, federations, baptisms, championships, wich resulted in vários interpretations. I resorted to a qualitative research with interviews by staff to three reat Masters of Belo Horizonte, which were protagonists of mining Capoeira during the Military Dictatorship. The responses showed resistance by some and te environmente from many, one soon realizes that the Military Regime hás brought many benefits to Capoeira.